ANALISIS KESESUAIAN DAN DAYA DUKUNG WISATA BAHARI DI PULAU MANGKIAN TAMAN WISATA PERAIRAN KEPULAUAN ANAMBAS - Yuwanda Ilham; Yusni Ikhwan Siregar; Deni Efizon (Berkala Perikanan Terubuk, 2018)
This study aims to determine the suistability and carrying capacity of marine tourism in Mangkian island of the Anambas Islands Marine Tourism Park. The survey was conducted in Mangkian Island, Batu Belah Village, East Siantan District, July to September 2017. Environmental parameters of coral cover (life form), and some aquatic biota strongly support marine tourism activities in this area. The results showed that The level of suitability of maritime tourism is at IKW value for coastal tourism category is very suitable, category diving tour accordingly, and snorkeling tour category according to conditional. The carrying capacity of the area in every tourism activity that is beach tourism 101 people / day, dive tourism 123 people / day and snorkeling tourism is recommended need rehabilitation first. Public perceptions on the management and development of marine tourism, especially in the ecological, economic and socio-cultural aspects of local communities.